Enhanced electrochromic coloration in Ag nanoparticle decorated WO3 thin films - Kharade, Rohini R.; Mali, Sawanta S.; Patil, Satish P.; Patil, Kashinath R.; Gang, Myong G.; Patil, Pramod S.; Kim, Jin H.; Bhosale, Popatrao N. (Electrochimica Acta, 2013)
WO3/Ag composite thin films were prepared by microwave assisted sol-gel synthesis (MW-SGS) of WO3 followed by vacuum evaporation of Ag nanoparticles and their enhanced electrochromic coloration was investigated. The composition and morphology of WO3 thin films with different thickness of Ag layer obtained by vacuum evaporation were investigated. Distinct plasmon absorption bands of Ag nanoparticle thin films were obtained. The optical band gap energy of WO3/Ag films decreased with increasing the Ag layer thickness. The surface of these films has been examined using X-ray photoelectron spectroscopy (XPS) to gain information about the chemical states of species present at surfaces. Experimental results indicated that the conductivity of the films increased after surface modification by Ag layer. To investigate the origin of enhanced electrochromic absorption in optical properties, working electrode consisting of WO3/Ag thin film was used and observed the optical properties during electrochemical reaction. It was found that composite electrode shows enhancement in electrochromic properties in terms of optical modulation (Delta OD) and coloration efficiency (eta). (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Ag2WO4; CIE coordinates; Electrochromism; SPR; WO3/Ag composite thin films

Adsorption of toxic Pb(II) on activated carbon derived from agriculture waste (Mahogany fruit shell): isotherm, kinetic and thermodynamic study - Patil, Suryakant A.; Suryawanshi, Umesh P.; Harale, Namdev S.; Patil, Sandip K.; Vadiyar, Madgonda M.; Luwang, Meitram N.; Anuse, Mansing A.; Kim, Jin H.; Kolekar, Sanjay S. (International Journal of Environmental Analytical Chemistry, 2022)
An adsorbent, mahogany fruit shell activated carbon(MFSAC), was derived from environmental friendly raw material, i.e. agriculture waste and explored for bench scale adsorption of toxic Pb(II). A facile MFSAC material was synthesised using a chemical activation method using concentrated sulphuric acid as an impregnating (activating) reagent. So derived adsorbent material was characterised by FTIR, XRD, BET, SEM, EDAX, TGA and XPS techniques to know the properties and plausible adsorption mechanism. Bench scale adsorption of toxic Pb(II) and maximum adsorption capacity of MFSAC were exhibited through batch adsorption experiments. The effect of physico-chemical parameters such as pH (1-7), MFSAC amount (0.5-5.0 g L-1), Pb(II) concentration (200-1000 mgL(-1)), contact period (60-600 min) and orbital shaking speed (60-200 rpm) was studied for maximum removal of Pb(II) upto 99.70 +/- 0.17%. The experimental data follow the Langmuir adsorption isotherm with a maximum monolayer adsorption capacity 322.28 mg g(-1)and pseudo-second-order kinetic uptake rate. The thermodynamic and temperature study revealed that the adsorption process was spontaneous and endothermic in nature (Delta H-o = 43.37 kJ mole(-1), Delta S-o = 158.02 J mol(-1)K(-1)). Most importantly, the MFSAC adsorbent was successfully regenerated and reused with conspicuous performance up to five consecutive cycles. The bench-scale adsorption with simple synthesis route, good stability and remarkable regeneration capability makes the MFSAC as an encouraging adsorbent for wastewater treatment.
Keywords: activated carbon; Adsorption; mahogany fruit shell; Pb(II); sulphuric acid